Performance and function of a desktop viewer at mayo clinic scottsdale - Eversman, William G. (Springer-Verlag, 2000)
A clinical viewing system was integrated with the Mayo Clinic Scottsdale picture archiving and communication system (PACS) for providing images and the report as part of the electronic medical record (EMR). Key attributes of the viewer include a single user log-on, an integrated patient centric EMR image access for all ordered examinations, prefetching of the most recent prior examination of the same modality, and the ability to provide comparison of current and past exams at the same time on the display. Other functions included preset windows, measurement tools, and multiformat display. Images for the prior 12 months are stored on the clinical server and are viewable in less than a second. Images available on the desktop include all computed radiography (CR), chest, magnetic resonance images (MRI), computed tomography (CT), ultrasound (U/S), nuclear, angiographic, gastrointestinal (GI) digital spots, and portable C-arm digital spots. Ad hoc queries of examinations from PACS are possible for those patients whose image may not be on the clinical server, but whose images reside on the PACS archive (10TB). Clinician satisfaction was reported to be high, especially for those staff heavily dependent on timely access to images, as well as those having heavy film usage. The desktop viewer is used for resident access to images. It is also useful for teaching conferences with large-screen projection without film. We report on the measurements of functionality, reliability, and speed of image display with this application.